Association between Body Mass Index (BMI) and the Incidence of Non-Alcoholic Fatty Liver Disease (NAFLD) - Villarsi, Devinda; Sungkar, Taufik (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: The prevalence of obesity among the population has risen dramatically due to a sedentary lifestyle. Obesity is a risk factor for the incidence of non-alcoholic fatty liver disease (NAFLD) and the prevalence of NAFLD rises to 90% in obese. NAFLD is a clinically silent disease that has become one of the most common causes of liver disease worldwide also due to multiple extrahepatic complications or comorbidities. This study aims to find the association between the Body mass index (BMI) and the incidence of NAFLD. Method: This analytic study with a cross-sectional design was conducted on the 3rd of July 2022 in Boho Village, Samosir District of North Sumatra. The participants were based on a simple random sampling that meets the criteria of inclusion. BMI was calculated as weight in kilograms divided by the square of height in meters (kg/m2), meanwhile, we performed an abdominal ultrasound to diagnose NAFLD. Statistical analyses were performed using SPSS and using Chi-Square test to see the association between BMI and the incidence of NAFLD. Result: Among of 48 participants, most of them were fatty liver grade 1 (31.25%), and Overweight/Obese (62.5%). The incidence of NAFLD is more prevalent in obese than non-obese participants (p = 0.0001). Conclusion: The most of participants were fatty liver grade 1 (31.25%), and Overweight/Obese (62.5%). There was a significant association between BMI and the incidence of NAFLD